PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL KOOPERATIF TIPE THINK TALK WRITE DENGAN MIND MAPPING PADA MATERI PEMANASAN GLOBAL UNTUK KELAS XI SMA - Asbiah, Asbiah; Irianti, Mitri; M. Nur, M. Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The learning device developed are learning device based on the TTW type kooperatif model with mind mapping on global warming material for class XI high school students, consisting of a Learning Implementation Plan (RPP), Student Worksheets (LKPD), and Learning Outcomes Test. The purpose of this study was to determine the validity of learning device based on the TTW type kooperatif with mind mapping on global warming material. This type of research is a Research and Development (R&D) with a 4D model design. The research instrument used was the RPP validation assessment sheets, LKPD, and the Learning Outcomes Test which were used by the validator to assess learning device. Data analysis in this study used descriptive analysis, by calculating the validity score of each indicator of the learning device. Based on the results of the validity data analysis, the average value of the validity of the lesson plans for the first meeting was 3.60 in the very high category and the average validity of the lesson plans for the second meeting was 3.56 with the very high category. The average validity of LKPD 01 was 3.58 with a very high category and the average validity of LKPD 02 was 3.67 with a very high category. The average validity of the Learning Outcomes Test was 3.76 with a very high category, so that the overall average learning device was 3.63 with a very high category. Thus the learning device based on the TTW kooperatif model with mind mapping is declared valid and suitable for use in global warming material in class XI SMA.Key Words: Physics Learning Device, Kooperatif Type TTW, Mind Mapping, Global Warming